REFLECTIONS ON THE CONDITION PROVIDED BY ART. 2 (1) GDPR: PERSONAL DATA TO BE PART OF A FILING SYSTEM - Silviu-Dorin ŞCHIOPU (Challenges of the Knowledge Society)
While the processing of personal data which are carried out in whole or in part by automated means are included in the material scope of Regulation (EU) 2016/679 of the European Parliament and of the Council of 27 April 2016 on the protection of natural persons with regard to the processing of personal data and on the free movement of such data, the latter applies to manual processing only in so far as personal data are part of or intended to be part of a filing system. Consultation, disclosure by transmission, dissemination or making available in any other way constitutes processing within the meaning of the General Data Protection Regulation (GDPR). If such processing is carried out by processing other than by automated means, in order to be covered by Regulation (EU) 2016/679 the data must be part of a filing system or be intended to be part of such a system. Thus, a question arises: to what extent making available by manual processing falls within the material scope of the General Data Protection Regulation? The fulfilment of the condition to form part of a filing system or to be intended to form part of a filing system depends on the specific situation and must be established on a case-by-case basis. On the other hand, the interpretation of the Court of Justice of the European Union, which has ruled that the concept of a ‘filing system’ covers data that are structured according to specific criteria which, in practice, enable them to be easily retrieved for subsequent use, without being necessary to include any search methods, must be taken into account in all cases. Nevertheless, if personal data processed manually falls outside the material scope of the General Data Protection Regulation because the data is not easily retrievable, it is still protected under the right to privacy as long as the data belongs to the sphere of private life.